2020
DOI: 10.1016/j.jobcr.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of sealing ability of gutta percha and resilon as root canal filling materials- a systematic review

Abstract: This systematic review aims to comparatively evaluate the sealing ability gutta-percha and resilon as root canal filling materials. A Medline search was conducted to identify in-vitro studies published between October 01, 2004 and October 01, 2019, conducted on human extracted teeth, published in English and testing the sealing ability of gutta-percha and resilon as root canal filling materials using fluid filtration method. The search identified fifty-five published articles. After a thorough screening, five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The competitive advantage of this material was supposed to be a monoblock with dentin [179][180][181], which unfortunately did not turn out to be true [182]. There has been dispute as to whether this material is more useful, as it has been recognized in some studies [168,178,184,194,211,215,216,230,[232][233][234][235][236][237][238][239][240][241][242][243][244][245], or whether gutta-percha provides the best filling and tightness in the root canal [160,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], especially after a longer time [208,209]. Many other evaluations and research results showed, and many dentists still believe, that Resilon cannot compete with gutta-percha.…”
Section: Summary and Final Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The competitive advantage of this material was supposed to be a monoblock with dentin [179][180][181], which unfortunately did not turn out to be true [182]. There has been dispute as to whether this material is more useful, as it has been recognized in some studies [168,178,184,194,211,215,216,230,[232][233][234][235][236][237][238][239][240][241][242][243][244][245], or whether gutta-percha provides the best filling and tightness in the root canal [160,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], especially after a longer time [208,209]. Many other evaluations and research results showed, and many dentists still believe, that Resilon cannot compete with gutta-percha.…”
Section: Summary and Final Commentsmentioning
confidence: 99%
“…The result of these differences is the other sealing abilities of individual materials, which have been the subject of numerous studies [168,193]. Gutta-percha provides the best filling and tightness in the root canal, which is reported in a large number of papers [160,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], especially after longer periods [208,209], and even better antimicrobial protection than all other filling materials, especially filling materials with a matrix made of polyester materials. In the works [193,[210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229], no differences were found in ensuring the tightness between gutta-percha and filling material with a matrix of polyester materials.…”
mentioning
confidence: 99%
“…Reinfection: root canal reinfection caused by root canal sealant dissolution and crown microleakage accounts for approximately 60% of RCT complications [18].…”
mentioning
confidence: 99%
“…In this paper, these issues are only discussed in general terms. For many years, gutta-percha has been the most commonly used natural material for filling root canals [110][111][112][113][114][115][116], and has even been recognized as the "gold standard of endodontics", and many studies have confirmed that it provides the best filling and tightness in the root canal [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131], especially after a long time [132,133] and with the selection of non-standard sealing materials [117,[134][135][136][137], although there are also contradictory reports in the literature [118,124, indicating the advantage of other filler materials and suggesting improper bonding of gutta-percha with dentin [159][160][161][162][163][164][165][166][167][168].…”
Section: Importance Of the Selection Of Filling Materials For Endodontic Treatmentmentioning
confidence: 99%